Rethinking Our Annual Congress—Meeting the Needs of Specialist Physicians by Partnering With Provincial Simulation Centers. Issue 1 (30th September 2022) - Daniel, Sam J.; Bouchard, Marie-Josée; Tremblay, Martin
Abstract: Canada's maintenance of certification programs for physicians has evolved to emphasize assessment activities. Our organization recognized the importance of offering more practice assessment opportunities to our members to enhance their practice and help them comply with a regulation from our provincial professional body related to ongoing continuing education. This led us to rethink our annual congress and enrich the program with a curriculum of interdisciplinary simulation sessions tailored to meet the needs of a broad audience of specialists. Our challenges are similar to those of many national specialty societies having limited access to simulation facilities, instructors, and simulation teams that can cover the breadth and scope of perceived and unperceived simulation needs for their specialty. Our innovative solution was to partner with local experts to develop 22 simulation sessions over the past three years. The response was very positive, drawing 867 participants. Over 95% of participants either agreed or strongly agreed that their simulation session (1) met their learning objectives, (2) was relevant for their practice, and (3) encouraged them to modify their practice. Narrative comments from a survey sent to the 2018 participants four months after their activity indicated several self-reported changes in their practice or patient outcomes. We were able to centralize offers from organizations that had previously worked in silo to develop simulation sessions meeting the needs of our members. Proposing simulation sessions allowed our organization to establish long-term partnerships and to expend our "educational toolbox" to address skill gaps not usually addressed during annual meetings.